Transnasal Esophageal Stricture Dilatation using Savary–Gilliard Dilator System—A Novel Approach - Goyal, Kartik; Bhargava, Narender; Dadhich, Sunil; Kumar, Naveen (Journal of Digestive Endoscopy, 2019)
Transnasal esophagoscopy is office-based procedure, used by otolarynologists and gastroenterologists for evaluation of dysphagia, odynophagia, esophageal stricture dilatations, and other numerous indications. Through the scope (TTS) balloon dilatation using ultrathin gastroscope is routine practice in patients with esophageal stricture (ES). Here, we are highlighting a case of post corrosive esophageal stricture with inadequate mouth opening dilated using savary gilliard (SG) dilator system transnasally.
Keywords: postcorrosive stricture; Savary–Gilliard dilator; transnasal route; ultrathin scope